Integrative Functional Genomics Implicated the Key T-/B-Cell Deficiency Regulator RAG1 in Transarterial Chemoembolization of Hepatocellular Carcinoma - Xu, Yeyang; Wang, Teng; Zeng, Jiajia; Wang, Bowen; Zhou, Liqing; Yang, Ming; Zhang, Li; Zhang, Nasha (Frontiers in Cell and Developmental Biology, 2021)
Transarterial chemoembolization (TACE) has significantly prolonged overall survival (OS) of unresectable hepatocellular carcinoma (HCC) patients. Unfortunately, there are still a portion of patients without therapeutic responses to TACE. Although genome-wide association studies identified multiple HCC susceptibility SNPs, it is still largely unclear how genome-wide identified functional SNPs impacting gene expression contribute to prognosis of TACE-treated HCC patients. In this study, we developed an integrative functional genomics methodology to identify gene expression-related SNPs significantly contributing to prognosis of TACE-treated HCC patients across the whole genome. Employing integration of data from expression quantitative trait locus (eQTLs) analyses of The Cancer Genome Atlas (TCGA) Liver hepatocellular carcinoma (LIHC) as well as the 1000 Genomes project, we successfully annotated 60 gene expression-related SNPs which are associated with OS of the TCGA patients. After genotyping these 60 SNPs in our TACE cohort, we identified four SNPs (rs12574873, rs12513391, rs34597395 and rs35624901) which are significantly associated with OS of HCC patients treated with TACE. For instance, multivariate Cox proportional hazards model indicated that the rs35624901 Deletion.Deletion (Del.Del) genotype carriers had markedly prolonged OS and a 55% decreased death risk compared with individuals with the GG genotype after TACE therapy (P=8.3×10-5). In support of this, the rs35624901 Del.Del genotype is correlated to higher expression of RAG1, a key T-/B-cell deficiency regulator. Our findings reported the first evidence supporting the prognostic value of four eQTL SNPs in TACE-treated HCC patients. Importantly, our data implicated that antitumor immunity might contribute to TACE efficiency for unresectable HCC patients.